2007
DOI: 10.1038/sj.sc.3102064
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic hypotension in the first month following acute spinal cord injury

Abstract: Study Design: Retrospective data analysis. Objectives: To determine prevalence of orthostatic hypotension (OH) in patients with spinal cord injury (SCI) during the acute rehabilitation period. Setting: Quaternary care spinal unit, Vancouver General Hospital, British Columbia, Canada Methods: Eighty-nine patients with acute SCI stratified by neurological level (cervical, 55 (62%); upper thoracic, 12 (13%); lower thoracic, 22 (25%)), and graded by American Spinal Injury Association standards. Non-invasive measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 26 publications
2
20
0
6
Order By: Relevance
“…It has been reported that orthostatic hypotension persists during the first month post-SCI in 74% of cervical motor complete patients. 43 Despite this figure, there has been only one study, which has investigated the effect of AB itself on orthostatic hypotension. 8 Although they found the AB to be effective at maintaining systolic blood pressure at pretilt levels when tilted to 451, they failed to assess the AB effect when sitting upright.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that orthostatic hypotension persists during the first month post-SCI in 74% of cervical motor complete patients. 43 Despite this figure, there has been only one study, which has investigated the effect of AB itself on orthostatic hypotension. 8 Although they found the AB to be effective at maintaining systolic blood pressure at pretilt levels when tilted to 451, they failed to assess the AB effect when sitting upright.…”
Section: Discussionmentioning
confidence: 99%
“…34 With time post injury, however, it has been demonstrated that individuals with thoracic SCI exhibit an increase in leg vascular resistance during head-up tilt that is consistent with that in the AB population. [35][36][37] The increase in leg vascular resistance was attributed to a local myogenic response triggered by changes in vascular pressure changes during head-up tilt.…”
Section: Organization Of the Autonomic Nervous Systemmentioning
confidence: 93%
“…[14][15][16][17][18][19] Gonzalez et al, 14 Huang et al, 16 and Levi et al 15 was limited by the grouping of lesion levels when the sample was stratified by completeness of injury, and the study by Vale et al 18 was limited by no statistical comparisons. Sidorov et al 19 conducted a comprehensive assessment of BP responses by lesion level and completeness of injury and reported no differences in SBP between individuals with cervical, high-thoracic, and low-thoracic incomplete SCI, whereas cervical complete SCI exhibited a lower SBP than thoracic complete SCI; unfortunately, no direct statistical comparisons were made between complete and incomplete SCI with the same injury level.…”
Section: Resting Blood Pressurementioning
confidence: 99%
“…Sidorov et al 19 reported that prevalence of orthostatic hypotension (OH) was reduced and persisted for less time in acute cervical incomplete versus complete SCI. Conversely, Illman et al 20 reported that there was a similar decline in BP in response to head-up tilt (HUT) in persons with incomplete versus complete injuries.…”
Section: Prevalence Of Blood Pressure Abnormalitiesmentioning
confidence: 99%